Pulse wave velocity and myocardial performance index in premature ovarian insufficiency. (4th March 2017) - Aksoy, Muhammed Necati Murat; Akdemir, Nermin; Kilic, Harun; Yilmaz, Sabiye; Akdemir, Ramazan; Gunduz, Huseyin
Abstract: Objective. Epidemiological studies suggest that women with loss of ovarian function at early ages may be especially burdened by cardiovascular disease (CVD). In this study, we aimed to evaluate pulse wave velocity (PWV) and myocardial performance index (MPI) in patients with premature ovarian insufficiency (POI). Design. We enrolled 51 female patients (mean age 38.9 ± 6.7 years) with POI and 49 healthy subjects (mean age 36.8 ± 5.2 years). All participants underwent a detailed echocardiographic examination and PWV measurement, which is basically the velocity of pulse wave travelling from carotid to femoral artery. Results. Both groups were similar with regard to age, body mass index (BMI) and left ventricular ejection fraction. When diastolic functions were assessed, patients with POI had higher mean E/E'ratio (9.3 ± 1.9 vs. 7.6 ± 1.6, p < 0.001). POI patients have impaired MPI (0.9 ± 0.5 vs. 0.5 ± 0.2, p < 0.001) comparing to healthy controls but PWV measurements did not differ between two groups (5.7 ± 0.8 vs. 5.6 ± 0.6 m/s, p = 0.48). Conclusions. This study showed POI patients might have impaired global left ventricular functions comparing to age matched healthy controls and this might reflect the effects of premature lack of estrogen (E) on women's cardiovascular (CV) system.